2011
DOI: 10.1007/s12560-011-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Virus Genome Quantification Does not Predict Norovirus Infectivity After Application of Food Inactivation Processing Technologies

Abstract: When determining the effect of food processing on the infectivity of any contaminating virus, it is necessary to distinguish unambiguously between infectious and noninfectious viruses present. However, this can be difficult in the particular case of noroviruses (NoVs) because no reliable cell culture model is available. The aim of this study was to assess the use of molecular methods-RT real-time PCR (RT-qPCR) and enzymatic treatment (ET) coupled to RT-qPCR-to quantify the infectivity of NoV after application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…1 log 10 unit reduction 6 log 10 unit reduction to effects on the virus genome and protein capsid integrity, but rather to effects on proteins associated with adhesion to and invasion of eukaryotic cells, which is in accordance with previous findings (Diez-Valcarce et al, 2011b;Kovač et al, 2012;Tang et al, 2010). As viruses which lose the ability to attach to the cells cannot cause infection, the only real assessment of risk to human health can be obtained by cell culture assay (e.g.…”
Section: Treatmentsupporting
confidence: 87%
“…1 log 10 unit reduction 6 log 10 unit reduction to effects on the virus genome and protein capsid integrity, but rather to effects on proteins associated with adhesion to and invasion of eukaryotic cells, which is in accordance with previous findings (Diez-Valcarce et al, 2011b;Kovač et al, 2012;Tang et al, 2010). As viruses which lose the ability to attach to the cells cannot cause infection, the only real assessment of risk to human health can be obtained by cell culture assay (e.g.…”
Section: Treatmentsupporting
confidence: 87%
“…In addition, TuV consists of at least 4 different genotypes, which display diverse histo-blood group antigen (HBGA) binding patterns mimicking those of human noroviruses (50). Like other investigators, we found that RNA quantitation after treatment of surrogate viruses with chlorine, alcohols, or HHP does not quantitate the loss of virus infectivity (22,23,47,51), although in some treatments an increase in RNA reduction did parallel an increase in infectivity reduction, as was apparent for the chlorine treatments of FCV and the alcohol treatments of MNV. Interestingly, treatments of human norovirus with chlorine, alcohols, and HHP demonstrated that GII viruses are more resistant than GI viruses, as measured by reductions of RNA by RT-qPCR.…”
Section: Fig 7 Reductions In Tuv Infectivity and In Tuv And Human Norsupporting
confidence: 65%
“…The maximum observed reductions in RT-qPCR signals following heat treatment can reach a plateau, and varies by study design, complicating direct comparison between studies. For surrogate viruses these maximum RT-qPCR signal reductions have been reported to range from b0.5 log 10 for MNV-1 (Diez-Valcarce et al, 2011;Li et al, 2012) to 2 log 10 for FCV F-9 (with RNase pre-treatment, Topping et al, 2009) and N4 log 10 for the bacteriophage MS2 (with proteinase K and RNase pretreatment, Pecson et al, 2009) for temperatures up to 85°C. These differences may be due to inherent differences in the heat resistance of these viruses.…”
Section: Discussionmentioning
confidence: 99%